The religious role of library Amongst Syuhada mosque library users in Kota Baru Yogyakarta - Nurdin Laugu; Sri Rohyanti Zulaikha (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2015)
This study is aimed at explaining the level of religious role of library amongst users of Syuhada mosque library that is located in Kota Baru Yogyakarta. The study uses the concept of Glock and Stark in defining the religiosity based on five dimensions, such as ideology and experience. In addition, other concepts related to the role of libraries that it can become in the forms of frequency of visits, type and subject of collections read, and the theme of religious subjects used. While the research uses a descriptive quantitative approach equipped with data collection techniques, such as questionnaire, interview, and observation. Its data analysis uses a method of percentage of a four-point Likert scale. The results are found that the religious role of library amongst Syuhada mosque library users achieves a high category, which is amounted to 76.80%. The number is an average of five indicators. The highest level is occupied by correlative links of the library effects to the level of religiosity of Syuhada mosque library users with a value of 85.60%. Conversely, the lowest one is located by the indicator of types of collection read by 70.75%. Based on the findings, the important recommendation that can be proposed is that the mosque library should be encouraged and developed because it obviously shows its correlative effects to the religious life of society.